Management Approach Against Pod Borer, Eucrysops Cnejus F. Attacking Yard Long Bean (Bangladesh Journal of Agricultural Research, 2022)
Several management approaches were evaluated against pod borer attacking yard long bean during April - July, 2019 at Entomology Research Field, Bangladesh Agricultural Research Institute (BARI), Gazipur. The management package namely sanitation + spraying bio-pesticide Antario (Package 1), sanitation + spraying bio-pesticide Spinosad 45 SC (Package 3) and sanitation + alternate spraying of Antario and Spinosad 45SC (Package 4) showed almost equal effectiveness in reducing flower and pod damage by pod borer and higher yield. But the management package sanitation + spraying bio-pesticide Antario (Package 1) appeared best as it provided the highest marginal benefit cost ratio (MBCR) (10.09), which was followed by sanitation + alternate spraying of Antario and Spinosad 45SC (6.97) (Package 4), and sanitation + spraying biopesticide Spinosad 45 SC (5.29) (Package 3). The effectiveness of sanitation +Bt kurstaki) (Package 2) was poor in respect of yield (12.06 tha-1) and MBCR (3.44).Bangladesh J. Agril. Res. 45(3): 233-237, September 2020